Students with Specific Learning Disabilities in Inclusive Settings: A study of Teachers' Self‐Efficacy. Issue 2 (31st January 2021) - Yakut, Ayse Dilsad
Abstract: Students with specific learning disabilities (SLD) are taught by general education teachers who may not respond positively to the inclusion of these students in their classrooms. Teachers' self‐efficacy is an important construct which is related to teachers' teaching and their willingness to include students with disabilities into their classrooms. The purpose of this study is to examine teachers' self‐efficacy toward teaching students with SLD. In the scope of the study, quantitative data were collected through a scale and an observation form from 200 general education teachers working in public elementary schools in a province of Turkey. Results indicated that the teachers who had students with SLD in their classroom felt more efficacious in teaching students with SLD. In addition, teachers reported that students with SLD had significantly lower problems in motor skills and significantly higher problems in math; attention and memory; and writing skills. Implications are discussed within the Turkish context.